Direito autônomo à prova - Amaral, Letícia Silva (2017)
Autonomous probative action in the new Code of Civil Procedure was born as an institute endowed with great potentialities, if presented in favor of the efficient process. It is a legal procedure, which relaxes the usual moment to carry out a process of preparation of a document for this purpose. The object of study is included in the research line, Process, Constitutionality and Tutorship of existential and patrimonial rights and aims to analyze the autonomous probation as a right of the plaintiff to know the facts and the usefulness of this procedural instrument to reduce litigiousness and as a mechanism capable of molding litigants aware of the risks of eventual demand. The realization of justice of a decision on the judgment of merit. In this context, approaches as premises of the right to early instruction, the intricacies of the legal procedure provided for the Civil Procedure Code of 2015 and relevant consequences.